An Indigenous Psychosocial Intervention for the Sexuality Problem of Men in Indonesian Urban Areas: A Systematic Literature Review - Rahmi, Kus Hanna; Fahrudin, Adi (Kuras Institute, 2024)
This systematic literature review aims to analyze the psychosocial and psychosexual interventions for addressing sexual health problems among men in urban areas of Indonesia, with a focus on indigenous practices such as Mak Erot. The review follows the PRISMA guidelines, involving a comprehensive search of multiple databases, selection of relevant studies, data extraction, and synthesis. List the databases and other sources searched: PubMed, Scopus, Google Scholar, and Indonesian local journals, grey literature, and reference lists of selected articles. Search term strategies with the combination used include; Psychosocial interventions